Teaching physical education in early childhood education: difficulties and possibilities - Quaranta, Silvia Cinelli; Rosrio Santoro Franco, Maria Amelia do; Betti, Mauro [UNESP] (Univ Estadual Sudoeste Bahia, 2016)
Who should teach Physical Education in Pre-School? This is still an unanswered question in Brazil. Historically speaking, class teachers have always done this job. However, there is a development today, which states that Physical Education professionals should teach this subject. In both cases, there are difficulties to overcome, such as teacher initial training; institutional conditions, epistemological ambiguities arising from childhood specificities and how fragile school pedagogical teams are. Having this complex environment as main setting, the aim of this study is to understand the pedagogical conditions and difficulties faced by Physical Education teachers in Pre-school and the possibilities to go beyond childhood pedagogical perspectives. The research, carried out in a town in the state of Sao Paulo, chose the job of Physical Education teachers in Preschool. We gathered data through questionnaires and interviews with teachers and educational supervisors, trying to triangulate data through content analysis and hermeneutical works of interpretation. Data has allowed us to understand that there is a clear need for special attention to teaching young children in undergraduate programs curricula, analyzing its specificities and formative possibilities, and what focus on children and their expressive moves should constitute pedagogical script to plan activities and meanings for learning. We have also concluded that pedagogical work with young children requires teaching staff to embrace continuous education and that activities should develop in an interdisciplinary manner.
Keywords: Physical Education; Pre-school Education; Pedagogical Practices